Workshop Pembuatan NPWP, Efin Dan Pelaporan SPT Tahunan Pph Badan Di Unit Koperasi Lintang Songo SMK Ma’arif NU Doro - Kusuma Wijaya; Siska Dewi; Fangela Myas Sari; Mukhsin Hadi (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Nearly 80% of Indonesia's state development and spending are financed by taxes. Given the importance of taxes for the continuity of government, the Directorate General of Taxes (DGT) must continue to innovate in updating tax policies to optimize tax revenue (HINELO & MONOARFA, 2018). Taxes are the largest national income revenue based on the State Revenue and Expenditure Budget (APBN). The Directorate General of Taxes has made various efforts to maximize tax revenue. It is hoped that the efforts made will be able to serve as a driving force for development that is and will occur. Taxpayers have several tax obligations, starting from making NPWP, paying taxes, to reporting the payment of tax payable to the Directorate General of Taxes using a notification letter (SPT). As technology develops, the digitization of the tax system also strengthens and makes all tax processes easier. Digital transformation of taxation has been going on for the past few years. One of the main developments is the digitization of the tax reporting system, from which PPh SPT was originally submitted manually to online using e-SPT (Wijaya, et al, 2021). To be able to report the e-SPT, taxpayers must be registered in the DGT online system first. After that, taxpayers can fulfill their obligations, namely submitting SPT reports using e-SPT to the Directorate General of Taxes. For this reason, taxpayers must have an EFIN registered with the DGT so they can make online transactions (Sari, et al, 2021). Electronic Filing Identification Number, abbreviated as EFIN, is a taxpayer identification number registered in the DGT system for online transactions. The obligation for taxpayers to have an EFIN to be able to carry out online transactions in the DGT's electronic system or electronic systems provided by Tax Application Service Providers is regulated in the Director General of Taxes Regulation Number PER-41/PJ/2015 concerning Security of Online Tax Service Electronic Transactions as amended by Regulation General of Taxes Number PER-06/PJ/2019 (Directorate General of Taxes, 2021).The purpose and target of community service at the Lintang Songo Cooperative Unit at the Ma'arif NU Doro Vocational School is so that administrators & members understand about making NPWP, Efin and reporting the Agency's Annual SPT at the Lintang Songo Cooperative Unit at Ma'arif NU Doro Vocational School. The number of participants was 35 people. The implementation method is carried out by presenting workshop material directly (offline) at SMK Ma'arif NU Doro. The output of this community service is in the form of publication of scientific journals in the ITS NU Pekalongan community service journal and cinematic videos of community service implementation.